Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To do this problem, you have to umm.... plug the numbers into each of the given equation until L.H.S. = R. H. S
the answer to this problem is..
D. y = -6x - 5
Lets check
(2,-17)
Substituting y = -17 and x = 2 , we get,
-17 = -6 (2) -5
-17 = -12 - 5
-17 = -17
(5 , -35)
Substituting y = -35 and x = 5 , we get,
-35 = -6 (5) - 5
-35 = -30 - 5
-35 = -35
So, the answer is D
the answer to this problem is..
D. y = -6x - 5
Lets check
(2,-17)
Substituting y = -17 and x = 2 , we get,
-17 = -6 (2) -5
-17 = -12 - 5
-17 = -17
(5 , -35)
Substituting y = -35 and x = 5 , we get,
-35 = -6 (5) - 5
-35 = -30 - 5
-35 = -35
So, the answer is D
D is the correct answer because if you plug in the points they equal the y value
-6(2) -5 = -17
-17 = -17
-6(5) - 5 = -35
-35 = -35
-6(2) -5 = -17
-17 = -17
-6(5) - 5 = -35
-35 = -35
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.